Modelo de optimización de flotas refrigeradas anchoveteras en una empresa pesquera peruana (LACCEI, 2024)
This paper shows a linear programming model whose main objective is the conversion of conventional fleets to refrigerated fleets with RSW system, in order to guarantee a better quality in the preparation of anchoveta fishmeal. Likewise, the proposed optimization model contemplates the maximization of profits associated with the increase of refrigerated fleets with the RSW system, complying with the costs established for said objective.